Noncirrhotic Portal Hypertension due to Nodular Regenerative Hyperplasia Treated with Surgical Portacaval Shunt. (21st August 2012) - Louwers, Lisa M.; Bortman, Jared; Koffron, Alan; Stecevic, Veslav; Cohn, Steven; Raofi, Vandad
Abstract : Nodular regenerative hyperplasia (NRH) is an uncommon condition, but an important cause of noncirrhotic intrahepatic portal hypertension (NCIPH), characterized by micronodules of regenerative hepatocytes throughout the liver without intervening fibrous septae. Herein, we present a case of a thirty-seven-year-old female with systemic lupus erythematosus (SLE) who was discovered to have significant esophageal varices on endoscopy for dyspepsia. Her labs revealed a slight elevation in the alkaline phosphatase and mild thrombocytopenia. Abdominal MRI revealed seven focal hepatic masses, splenomegaly, no ascites, and a patent portal vein. Ultrasound-guided core biopsy was reported as focal nodular hyperplasia. However, her varices persisted despite treatment with beta-blockers and four additional upper endoscopies with banding. She was subsequently referred for a surgical opinion. At that time, given her history of SLE, azathioprine use, and portal hypertension, suspicion for NRH was raised. Given her normal synthetic function and lack of parenchymal liver disease, the patient was offered surgical shunting. During shunt surgery, a liver wedge biopsy was also performed and this confirmed NRH. An upper endoscopy six weeks after shunting verified complete resolution of varices. Currently, fifteen months after surgery duplex ultrasonography demonstrates shunt patency and the patient is without recurrence of her portal hypertension.